Altered Serotonin 2A (5-HT2A) Receptor Signaling Underlies Mild TBI-Elicited Deficits in Social Dominance - Collins, Sean M.; O’Connell, Christopher J.; Reeder, Evan L.; Norman, Sophia V.; Lungani, Kainat; Gopalan, Poornima; Gudelsky, Gary A.; Robson, Matthew J. (Frontiers in Pharmacology, 2022)
Various forms of traumatic brain injury (TBI) are a leading cause of disability in the United States with the generation of neuropsychiatric complications such as depression, anxiety, social dysfunction, and suicidality being common comorbidities. Serotonin (5-HT) signaling is linked to psychiatric disorders, however the effects of neurotrauma on normal, homeostatic 5-HT signaling within the central nervous system (CNS) have not been well characterized. We hypothesize that TBI alters specific components of 5-HT signaling within the CNS and that the elucidation of specific TBI-induced alterations in 5-HT signaling may identify novel targets for pharmacotherapies that ameliorate the neuropsychiatric complications of TBI. Herein, we provide evidence that closed-head blast-induced mild TBI (mTBI) results in selective alterations in cortical 5-HT2A receptor signaling. We find that mTBI increases in vivo cortical 5-HT2A receptor sensitivity and ex vivo radioligand binding at timepoints corresponding with mTBI-induced deficits in social behavior. In contrast, in vivo characterizations of 5-HT1A receptor function revealed no effect of mTBI. Notably, we find that repeated pharmacologic activation of 5-HT2A receptors post-injury reverses deficits in social dominance resulting from mTBI. Cumulatively, these studies provide evidence that mTBI drives alterations in cortical 5-HT2A receptor function and that selective targeting of TBI-elicited alterations in 5-HT2A receptor signaling may represent a promising avenue for the development of pharmacotherapies for TBI-induced generation of neuropsychiatric disorders.